Experimental diesel spray characterization of the medium-duty injector with single- and multi-hole nozzle configurations under non-reacting, non-vaporizing conditions - Park, Ji-Woong; Jouzdani, Shirin; Tzanetakis, Tom; Schmidt, Henry; Atkinson, William; Naber, Jeffrey; Pei, Yuanjiang; Tao, Feng; Garg, Rajesh; Langenderfer, David; Zhang, Yu; Som, Sibendu (Frontiers in Mechanical Engineering, 2022)
Characteristics of diesel sprays injected through Cummins medium-duty ISB injectors were studied experimentally in an optically accessible constant-volume combustion vessel. The experiments were performed with ultra-low-sulfur diesel (ULSD) under non-reacting and non-vaporizing conditions, including different ambient gas densities (23–65 kg/m3), injection pressures (500–1500 bar), and injection duration times (0.5–1.5 ms). The ambient temperature of the vessel was maintained at a room temperature of 313K for all the tests. A systematic comparison was made between single-hole (SH) and multi-hole (MH) injector configurations. A plume-to-plume variation in spray penetration length was observed for various operating conditions. A substantial deviation was observed for a specific hole against the averaged plume, indicating that arbitrary selection of the plume index may result in inaccurate spray characterization of the MH injector. The penetration length of the MH injector was shorter than that of the SH injector under the same operating conditions, indicating that a spray model calibrated on SH injector data may not accurately predict the transient spray behavior of the MH injector under practical engine simulations. A square-root correlation of the spray penetration length was applied for both the SH and MH injectors. The spray penetration length and dispersion angles of the ISB SH injector were also compared against those of the heavy-duty Cummins ISX SH injector. While the ISX SH injector showed a faster penetration against the ISB SH injector, the dispersion angle was similar. The differences in spray penetration between ISB and ISX injectors followed the expected trend according to their nozzle hole diameters.